Evaluating the emerging adsorbents for performance improvement of adsorption desalination cum cooling system. (March 2023) - Asfahan, Hafiz M.; Sultan, Muhammad; Farooq, Muhammad; Ibrahim, Sobhy M.; Imran, Muhammad; Askalany, Ahmed A.; Shahzad, Muhammad W.; Zhou, Yuguang; Sajjad, Uzair; Feng, Yong-qiang
Abstract: The study aims to investigate the emerging adsorbents for adsorption desalination cum cooling system (ADCS) from the viewpoints of water production potential (WPP), specific cooling potential (SCP), energy required (ER), and coefficient of performance (COP). In this regard, five kinds of covalent triazine framework (CTF), five kinds of porous organic polymer (POP), and five kinds of ionogel based adsorbents are investigated as compared to five kinds of conventional silica-gel (SG) adsorbents. The well-known Dubinin-Astakhov (D-A) model, Clausius–Clapeyron equation, and ideal cycle governing equations were used to estimate adsorption equilibrium, isosteric heat of ad/desorption and the performance indicators, respectively. Among the studied adsorbents, A ++, RD, Syloid 72FP + 57 wt% Emim-Ac, bipy-CTF500, and PS-II adsorbents produced relatively good results. However, nearly equivalent WPP (0.29 kg/kg/cycle) and SCP (710 kJ/kg/cycle) were estimated for A ++, RD, bipy-CTF500 using ER of 2979, 2988 and 2992 kJ/kg/cycle, respectively. The PS-II adsorbent shows the WPR of 0.33 kg/kg/cycle and SCP of 790 kJ/kg/cycle using ER of 2983 kJ/kg/cycle. The performance estimated for Syloid 72FP + 57 wt% Emim-Ac found 5.6 folds higher as compared to A ++ and could utilized as a potential adsorbent for ADCS. The COP of all the studied adsorbents estimated in range of 0.74 to 0.93. Graphical abstract: Unlabelled Image Highlights: SG, Ionogel, CTF, and POP based adsorbents are studied for ADCS. Steady-state modeling of single-bed ADCS for various adsorbents were performed. Performance parameters of emerging adsorbents are compared with SG. Syloid 72FP + 57 wt% Emim-Ac/H2 O pair improve 80% of ADCS productivity than A ++ .